Scientific and pedagogical approaches to the development of innovative educational technologies - Kosenko, A. V.; Pererva, P. G. (ФОП Панов А. М., 2023)
Organization of innovative activities in the field of education economic disciplines and the development of modern education technology is based on a number of special principles: establishment of economic profitability of skills and knowledge; comprehensive consideration of applied developments and research; focus on the specifics of the regional economic system.
Науково-педагогічні підходи до розробки інноваційних освітніх технологій
Keywords: pedagogy; methodological approaches; higher education; educational technologies